A Study Comparative: Cooperative Learning Model and Process Skills - Kamid Kamid; Husni Sabil; Wardi Syafmen; Miftahul Zannah Azzahra (Universitas Pendidikan Ganesha, 2022)
Cooperative Learning Model and Process Skills in the personality of each student are very important to have to maximize the activities and learning outcomes of each student. This study aims to analyze the differences and also the relationship between student process skills and student responses to the jigsaw learning model in mathematics subjects. This research is important so that teachers or educators know the students' process skills and student responses to the jigsaw learning model. The urgency of this research is as a reference for educators in carrying out teaching so that it is more optimal by using the jigsaw learning model to improve students' process skills in mathematics subjects at SDN/MIS. This type of research is quasi-experimental quantitative research by comparing 8 classes using a jigsaw model with material velocity and discharge. The sample in this study was 288 elementary school students, the sampling technique was purposive sampling. This study uses quantitative data analysis with the help of SPSS 25 statistics. Based on the correlation test of student process skills and student responses to the jigsaw model with speed and discharge material, there is a relationship between student process skills and student responses to the jigsaw model with speed and discharge material.